ANALISIS PENOKOHAN DALAM GEGURITAN BATUR TASKARA - I Putu Agus Aryatnaya Giri; Putu Eddy Purnomo Arta (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
The main character in Geguritan Batur Taskara (GBT) is Batur Taskara. Whereas the secondary figures are Raja Patali, Maya's Wife, and Batur Taskara's son. As well as complementary figures are the servants of the king, Empu Bajra Satwa, Pranda Wife, and Hyang Wirocana. Analysis of characterizations in GBT, among others; 1) Batur Taskara is the main character in Geguritan Batur Taskara because he fully supports the story / gets the most portrayal of the figures from other figures. When viewed from the psychological aspect, the Batur Taskara figure is described as a figure who is not good because it always creates chaos in Patali. However, Batur Taskara is not always portrayed as a figure who always does evil. In the end he regretted all the evil deeds he had done and wanted to repent. 2) Raja Patali, from the psychological and sociological aspects, was a king who was highly respected by his people because he ruled in a strict and peaceful manner. 3) Maya's wife is the wife of Batur Taskara who is described as an evil and very devious woman. With her beauty and guile, she tried to win Batur Taskara's heart. 4) Batur Taskara's son is portrayed as an intelligent child and very loyal to his mother, 5) The king's servants are portrayed as being very loyal but rash in their actions. 6) Empu Bajra Satwa has a very high sense of humanity and love because even though he knows that Batur Taskara has committed many crimes, he still wants to accept Batur Taskara as his student, 7) Pranda This wife also has a sense of humanity and love that very high because they are willing to accept Batur Taskara in Pasraman very friendly. 8) Hyang Wirocana is a figure of God who lives in a grave with a good character because he forbids Batur Taskara from returning to Patali at Badra Wada because he could find death.